Heat transfer in MHD mixed convection flow of a ferrofluid along a vertical channel - Gul, Aaiza (Public Library of Science, 2015)
This study investigated heat transfer in magnetohydrodynamic (MHD) mixed convection flow of ferrofluid along a vertical channel. The channel with non-uniform wall temperatures was taken in a vertical direction with transverse magnetic field. Water with nanoparticles of magnetite (Fe3O4) was selected as a conventional base fluid. In addition, non-magnetic (Al2O3) aluminium oxide nanoparticles were also used. Comparison between magnetic and magnetite nanoparticles were also conducted. Fluid motion was originated due to buoyancy force together with applied pressure gradient. The problem was modelled in terms of partial differential equations with physical boundary conditions. Analytical solutions were obtained for velocity and temperature. Graphical results were plotted and discussed. It was found that temperature and velocity of ferrofluids depend strongly on viscosity and thermal conductivity together with magnetic field. The results of the present study when compared concurred with published work